The clinical effectiveness of cognitive behavior therapy and an alternative medicine approach in reducing symptoms of depression in adolescents - Charkhandeh, Mansoureh; Abu Talib, Mansor; Hunt, Caroline Jane (Elsevier Ireland, 2016)
The main aim of the study was to investigate the effectiveness of two psychotherapeutic approaches, cognitive behavioral therapy (CBT) and a complementary medicine method Reiki, in reducing depression scores in adolescents. We recruited 188 adolescent patients who were 12-17 years old. Participants were randomly assigned to CBT, Reiki or wait-list. Depression scores were assessed before and after the 12 week interventions or wait-list. CBT showed a significantly greater decrease in Child Depression Inventory (CDI) scores across treatment than both Reiki (p<.001) and the wait-list control (p<.001). Reiki also showed greater decreases in CDI scores across treatment relative to the wait-list control condition (p=.031). The analyses indicated a significant interaction between gender, condition and change in CDI scores, such that male participants showed a smaller treatment effect for Reiki than did female participants. Both CBT and Reiki were effective in reducing the symptoms of depression over the treatment period, with effect for CBT greater than Reiki. These findings highlight the importance of early intervention for treatment of depression using both cognitive and complementary medicine approaches. However, research that tests complementary therapies over a follow-up period and against a placebo treatment is required.